AUTHORS OF AIRLINE SMOKING BAN KICK OFF RENEWAL DRIVE - DURBIN,D (Tufts Archival Research Center, 2007)
News release from the office of Congressman Dick Durbin regarding the renewal of the ban on cigarette smoking on airplanes. Cites the support for the ban from the general public as a driving force behind renewing it.